Development of a solar radiation model considering the hourly sunshine duration for all-sky conditions – A case study for Beijing, China. (1st August 2020) - Chang, Kai; Zhang, Qingyuan
Abstract: The hourly values of solar radiation are more useful than daily values for some specific applications such as building thermal simulation, and photovoltaic system; however, the existing solar models for estimating hourly values are much less than those for estimating daily ones. Furthermore, most of the hourly solar models have been developed for clear-sky conditions only, not for all-sky conditions. In this study, two hourly solar models for all-sky conditions (Nimiya model and Zhang model) are tested and modified for Beijing, China. The results show that the modified Nimiya model using the three-hour temperature difference instead of the daily mean one has good performance with correlation coefficient of 0.948 and RMSE of 92.08 W/m 2 . With consideration of hourly sunshine duration which is rarely utilized in the current solar models, a new solar model is developed for all-sky conditions based on regression analysis. The RMSE of the new proposed model is 84.59 W/m 2, which is reduced by 33.88% compared with the Zhang model for Beijing. The hourly sunshine duration is an effective parameter for hourly solar models. More locations are needed for testing the proposed model in the future study. Highlights: The hourly sunshine duration is introduced and analyzed in empirical solar models for all-sky conditions. The Nimiya hourly solar model is introduced and modified for Beijing in this study. The new hourly solar model is proposed for all-sky conditions.